Copper coordination compounds based on bis-quinolylhydrazone of 2, 6-diacetylpyridine: Synthesis, structure and cytotoxic activity. (15th March 2023) - Tupolova, Yuliya P.; Shcherbakov, Igor N.; Popov, Leonid D.; Vlasenko, Valery G.; Gishko, Konstantin B.; Kapustina, Anna A.; Berezhnaya, Aleksandra G.; Golubeva, Yuliya A.; Klyushova, Lyubov S.; Lider, Elizaveta V.; Lazarenko, Vladimir A.; Minin, Vadim V.; et al.
Graphical abstract: Abstract: Bis -hetarylhydrazone H2 L (1), a condensation product of 2, 6-diacetylpyridine with 2-hydrazinoquinoline, has been synthesized. By reaction of 1 with Cu(II) nitrate and perchlorate binuclear mixed-valence coordination compounds [Cu I Cu II (H2 L)2 ](NO3 )3 ⋅2H2 O (2) and [Cu I Cu II (H2 L)2 ](ClO4 )3 (3) were obtained. Cu(I) Ion in the compounds 2, 3 is in the distorted tetrahedral N -donor environment, while Cu(II) center is in the distorted octahedral one. Cu(II) Chloride and bromide form with 1 asymmetric mononuclear compounds with composition [Cu(H2 L)Cl]Cl (4) and [Cu(H2 L)Br]Br (5) with tetragonal–pyramidal coordination polyhedron. The structures of the compounds were studied by means of NMR, IR, ESR, UV–vis, X-ray absorption spectroscopy and X-ray single crystal diffraction methods. The effect of compounds on viability of the Hep-2 and HepG2 cell lines was investigated in vitro . The study showed that 1 is non-toxic at tested concentrations (1–100 μM), while all the complexes exhibit significant dose-dependent cytotoxic effect. It is shown that compounds 2 –5 demonstrate higher cytotoxicity towards considered cancer cell cultures than widely used commercial anticancer pharmaceuticals – cisplatin and carboplatin. Quantum-chemical modeling of the structure of the ligand 1 and its complexes was performed using density functional theory at B3LYP/6-311G(d) level of theory. Molecular electrostatic potential (MEP) and average local ionization energy (ALIE) surfaces were calculated to rationalize the reactive properties of the compounds.